International scientific and practical conference “Current issues of physical education and sports in modern socio-economic conditions” (Cheboksary, October 31 – November 1, 2024) - Talantseva, Valentina K.; Petrova, Tatyana N.; Shilenko, Olga V.; Pyanzina, Nadezhda N. (Физическое воспитание и студенческий спорт)
The paper presents a report on the International scientific and practical conference “Current issues of physical education and sports in modern socio-economic conditions”, held on October 31 – November 1, 2024 at the Chuvash State Agrarian University in Cheboksary.